Analisis Tingkat Literasi Keuangan Mahasiswa Program Studi Manajemen Keuangan Perbankan Di Politeknik LP3I Tasikmalaya - Aprilia, Dela; Bahiyyah, Khariidatul; Nugraha Irawan Surayuda, Rama (Jurnal Ekonomi Bisnis dan Manajemen, 2025)
This study aims to analyze the level of financial literacy among students of the Banking Financial Management study program at LP3I Polytechnic Tasikmalaya. Financial literacy refers to the ability to understand and manage finances effectively. The research method used is a descriptive quantitative approach, which addresses the problem by presenting, analyzing, and interpreting numerical data to provide an overview of a particular phenomenon. The results of the study indicate that the overall financial literacy level of students in the Banking Financial Management program at LP3I Polytechnic Tasikmalaya falls into the high category, with an average score of 4.13. Students demonstrate a very high level of financial literacy in indicators such as basic knowledge of personal finance, skills in using financial products and services, and money management.